Automatic threshold selection for automated visual surveillance - Çelik, T; Kabakli, T; Uyguroglu, M; Özkaramanli, H; Demirel, H (IEEE, 2004)
Automated Visual surveillance systems mostly depend upon effective background subtraction technique. Most of the background subtraction techniques mainly suffer from parameter updates for threshold selection. Here a new threshold selection technique which is found while system trains to learn background, is proposed.
IEEE 12th Signal Processing and Communications Applications Conference -- APR 28-30, 2004 -- Kusadasi, TURKEY